In the Mountains - Arnim, Elizabeth von (Saga Egmont, 2023)
The story is written in first person as a journal. Our narrator is a tired English woman who, after WWI, escapes ambiguous personal troubles in London and seeks refuge at her chalet among the Swiss Alps. As she starts to gain strength, two English women, also of ambiguous personal circumstances, show up literally on her doorstep.